Stanisław Sheybal i jego rola w krzewieniu kultury plastycznej i edukacji artystycznej w Polsce - Lewińska, Beata (Saeculum Christianum. Pismo Historyczne, 2019)
The figure of Stanisław Sheybal (1891-1976), painter, distinguished photographer, co-organizer of many cultural and artistic projects, has been the subject of many studies. Usually, the focus was on Sheybal's artistic activities in the field of photography, especially during his work at the Krzemieniecki Secondary School. However, his role as an educationalist and organizer of artistic life, especially after the Second World War, has been insufficiently highlighted. Before the Second World War, Stanisław Sheybal was a teacher at the Krzemieniec Secondary School. From 1946 he was the head of art schools. Between 1954-1957 he was the head of the Art Section of the Educational Centre for Art Education. At the same time, he was the director of the Visual Culture Centre in Krakow and then, from 1949, he was a teacher at the High School of Visual Arts in Warsaw. In 1949 he was also nominated as professor at the Warsaw Academy of Visual Arts, and then he was nominated as professor at the Łódź Academy of Visual Arts. At that time, he was the inspector of visual arts schools and lectured at the Pedagogical College of the Academy of Fine Arts in Warsaw. The artist was the organizer and co-organizer of trainings for music and art teachers as well as teachers of visual arts in art schools. He contributed to the development of visual arts staff. This article shows the figure of the artist primarily as a pedagogue and educationalist of visual art (in public schools) and artistic education (in art schools). The artist's profile has been presented in a broader context. The article uses Sheybal's reflections on teaching, based on the artist's memories and published methodological articles.